Buccal Patch: A New Avenue for Better Patient Compliance in Management of Diabetes Mellitus: Pharmaceutical sciences- Pharma - Kumar Pandey, Harsh; Kumar Yadav, Anurag; Vimal Arora, Dr. (International Journal of Life Science and Pharma Research, 2023)
Diabetes is a persistent metabolic condition that affects many individuals globally. To manage diabetes, patients need totake medication regularly, and the buccal patch has become a promising drug delivery option for this purpose. This review articlehighlights the potential of buccal patches as a novel approach to enhance patient compliance in treating diabetes mellitus. Byexploring the advantages of buccal patches as a non-invasive drug delivery system, this article emphasizes their potential to improvemedication adherence, thereby contributing to better management of diabetes mellitus. This article aims to evaluate the role ofbuccal patches in improving patient compliance in the treatment of diabetes mellitus. With the increasing global burden of diabetes,ensuring patient adherence to medication regimens is crucial for achieving optimal therapeutic outcomes. Traditional treatmentmethods often require frequent injections or oral administrations, which may lead to poor compliance due to various factors suchas fear of injections, inconvenience, or forgetfulness. Reviewing the literature on buccal patches as an alternative drug deliverysystem, this article explores their advantages in enhancing patient compliance. Buccal patches adhere to the inner lining of thecheek, providing a convenient and non-invasive route of drug administration. This approach eliminates the need for injections andreduces the frequency of oral medication intake, improving patient acceptance and adherence to treatment regimens. Furthermore,this article highlights the potential of buccal patches in delivering medications directly into the systemic circulation through thehighly vascularized oral mucosa. By bypassing first-pass metabolism in the liver, buccal patches can achieve higher drugconcentrations and improve therapeutic effects. Presenting the benefits of buccal patches for diabetes treatment encourages furtherresearch and development. So, the conclusion of this article is to promote awareness among healthcare professionals and patientsabout the potential of buccal patches as a patient-friendly approach to enhance compliance in the management of diabetes mellitus.